Characteristics and outcome of primary sclerosing cholangitis associated with inflammatory bowel disease in Asian children - Way Seah Lee; Sivaramakrishnan Venkatesh Karthik; Ruey Terng Ng; Sik Yong Ong; Christina Ong; Fang K. Chiou; Shin Yee Wong; Seng Hock Quak; Marion Margaret Aw (Pediatrics and Neonatology)
Background: Current knowledge on the clinical features and natural history of childhood primary sclerosing cholangitis – inflammatory bowel disease in Asia is limited. We described the presenting features and natural history of primary sclerosing cholangitis-inflammatory bowel disease seen in a cohort of Southeast Asian children. Methods: We conducted a retrospective review of childhood primary sclerosing cholangitis-inflammatory bowel disease from three tertiary centers in Singapore and Malaysia. Results: Of 24 patients (boys, 58%; median age at diagnosis: 6.3 years) with primary sclerosing cholangitis-inflammatory bowel disease (ulcerative colitis, n = 21; Crohn's disease, n = 1; undifferentiated, n = 2), 63% (n = 15) were diagnosed during follow-up for colitis, and 21% (n = 5) presented with acute or chronic hepatitis, 17% (n = 4) presented simultaneously. Disease phenotype of liver involvement showed 79% had sclerosing cholangitis-autoimmune hepatitis overlap, 54% large duct disease, and 46% small duct disease. All patients received immunosuppression therapy. At final review after a median [±S.D.] duration follow-up of 4.7 [±3.8] years, 12.5% patients had normal liver enzymes, 75% persistent disease, and 12.5% liver failure. The proportion of patients with liver cirrhosis increased from 13% at diagnosis to 29%; 21% had portal hypertension, and 17% had liver dysfunction. One patient required liver transplant. Transplant-free survival was 95%. For colitis, 95% had pancolitis, 27% rectal sparing, and 11% backwash ileitis at initial presentation. At final review, 67% patients had quiescent bowel disease with immunosuppression. One patient who had UC with pancolitis which was diagnosed at 3 years old developed colorectal cancer at 22 years of age. All patients survived. Conclusions: Liver disease in primary sclerosing cholangitis-inflammatory bowel disease in Asian children has variable severity. With immunosuppression, two-thirds of patients have quiescent bowel disease but the majority have persistent cholangitis and progressive liver disease. Key Words: sclerosing cholangitis, ulcerative colitis, progressive